Dry eye syndrome among patients with type II diabetes mellitus in a tertiary care centre in South India - Prasad, Shimna Clara; Goudinho, Sheldon James; Koshy, Blessy Mary (Nepalese Journal of Ophthalmology, 2022)
Introduction: One of the leading causes of dry eye syndrome (DES) is found to be diabetes mellitus (DM). The current study was conducted to detect possible tear film anomalies among diabetic individuals attributable to dry eye. The study aimed to assess the proportion of dry eye syndrome among patients with Type 2  diabetes mellitus. Materials and methods: Two hundred patients with Type 2 diabetes mellitus who came to the Ophthalmology OPD from October 2018 to November 2020 in the 29-60 years age group were included in the study. Patient data, diabetic history, dry eye symptoms, blood sugar values and tests to measure tear volume and tear film instability were carried out among patients and dry eyes were graded.Results: The proportion of patients with dry eye symptoms among Type 2 diabetes mellitus were 61%. Mild dry eye syndrome was observed in 27%, moderate dry eye syndrome in 59% and severe dry eye syndrome in 14%. A statistically significant difference (p